2023
DOI: 10.3390/antibiotics12030538
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Therapy Duration for Bloodstream Infections Caused by Pseudomonas aeruginosa or Acinetobacter baumannii-calcoaceticus complex: A Retrospective Cohort Study

Abstract: Background: Ideal therapy duration for Pseudomonas aeruginosa or Acinetobacter baumannii-calcoaceticus complex (ABC) bloodstream infections (BSI) is not defined, especially in the context of carbapenem resistance. In this study, we compared short- (≤7 days) and long-term (>7 days) antimicrobial therapy duration for these infections. Methods: We performed a retrospective cohort study in two tertiary-care hospitals in Porto Alegre, Brazil, from 2013 to 2019. Eligible patients aged ≥18 years were included and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Siddharth Swamy et al [ 15 ] compared the effectiveness of short-course and prolonged-course treatments in a retrospective analysis of 178 patients with gram-negative BSI and found that short-course therapy for gram-negative bacteremia yielded comparable rates of clinical response (78.6% vs 80.6%, P = .202) and microbiological cure (83.3% vs 91.7%, P = .690). Rodrigues et al [ 16 ] indicated that short-term therapy was not associated with 30-day mortality(hazard ratio [HR] = 1.01, 95% CI .47–2.20, P = .98), Bae et al [ 17 ] included 290 uncomplicated PA BSI and found that no significant difference in the risk of recurrence or 30 day mortality between the prolonged-course and short-course groups (HR = 0.68, 95% CI = .34–1.36, P = .28) and the recurrence of PA infection within 180 days (HR = 0.57, 95% CI = .29–1.10, P = .09). However, several retrospective studies involving immunocompromised populations are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Siddharth Swamy et al [ 15 ] compared the effectiveness of short-course and prolonged-course treatments in a retrospective analysis of 178 patients with gram-negative BSI and found that short-course therapy for gram-negative bacteremia yielded comparable rates of clinical response (78.6% vs 80.6%, P = .202) and microbiological cure (83.3% vs 91.7%, P = .690). Rodrigues et al [ 16 ] indicated that short-term therapy was not associated with 30-day mortality(hazard ratio [HR] = 1.01, 95% CI .47–2.20, P = .98), Bae et al [ 17 ] included 290 uncomplicated PA BSI and found that no significant difference in the risk of recurrence or 30 day mortality between the prolonged-course and short-course groups (HR = 0.68, 95% CI = .34–1.36, P = .28) and the recurrence of PA infection within 180 days (HR = 0.57, 95% CI = .29–1.10, P = .09). However, several retrospective studies involving immunocompromised populations are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of consensus for specific duration for MDR infections and in particular CRAB. Studies on patients with MDR infections with VAP and BSI have used a range of 7-22 days of therapy [101][102][103]. RCT and prospective studies on VAP have shown no difference in mortality with shorter courses of 3-8 days [104][105][106].…”
Section: Duration Of Therapymentioning
confidence: 99%